Fabrication of CdS nanowires on TiO2 nanorods for solar cell application. (1st March 2016) - Pishekloo, S. Piri; Dariani, R.S.; Salehi, F.
Abstract: A composition of CdS nanoparticles and nanowires were deposited on TiO2 nanorods by successive ionic layer adsorption and reaction method grown on Ti substrate. CdS/TiO2 /Ti device were used as photoanode in solar cell. Efficiency, short circuit current, and open circuit voltage were measured. Also, electron life time in each Fermi level and order of recombination were obtained by open circuit voltage decay and short circuit photocurrent interrupt voltage; respectively. Our results showed that there is an optimum composition of CdS nanoparticles and nanowires which improves solar cell properties of this type of cell.